Some Convergence and Stability Results for Two New Kirk Type Hybrid Fixed Point Iterative Algorithms. (28th January 2014) - Gürsoy, Faik; Karakaya, Vatan
Abstract : We introduce Kirk-multistep-SP and Kirk-S iterative algorithms and we prove some convergence and stability results for these iterative algorithms. Since these iterative algorithms are more general than some other iterative algorithms in the existing literature, our results generalize and unify some other results in the literature.